Investigating teachers’ and graduates’ remarks on the translation of English modals into Vietnamese provided by Google Translate - Nguyen, Huynh Trang; Khau, Hoang Anh (Penerbit Universiti Kebangsaan Malaysia, 2021)
Due to demands of using English for work, study and entertainment, more Vietnamese people have tended to use Google Translate to help translate English into Vietnamese and vice versa. This tool has become popular in these situations. However, can this tool translate English modal verbs expressing social functions into Vietnamese? To obtain the data for the study, the authors used the English source extracted from the grammar course book by Celce-Murcia and Larsen-Freeman (1999) which was fed into Google Translate for their Vietnamese versions. The source was related to making requests, giving advice, expressing potential realization, expressing desire, giving invitation and making preference. The study also recruited 11 experienced Vietnamese-speaking teachers of English and 21 Vietnamese-speaking graduates of English to give their remark on these translation texts which were sent to them via email and the social media platform Zalo. The findings showed that Google Translate was able to keep the intended meanings of many social functions through using the English modal verbs when transferring these functional texts into Vietnamese. The results also uncovered that most of the teachers and graduates agreed with these translated texts provided by Google Translate. Besides, both groups had a quite common point of view that Google Translate were unable to translate the past forms of the English modal verbs for more indirect or polite intention when they were transferred into Vietnamese. Some recommendations to help improve English- Vietnamese translation provided by Google Translate were also included.